Предмет: Алгебра, автор: m7097264

помогите пожалуйста ​

Приложения:

Ответы

Автор ответа: 51742554
1

x+2\frac{1}{3} +3\frac{1}{9} -1\frac{1}{12} =5\frac{7}{12} \\ x+\frac{7}{3} +\frac{28}{9} -\frac{13}{12} =\frac{67}{12} \\ x=-\frac{7}{3} -\frac{28}{9} +\frac{13}{12} +\frac{67}{12}\\ x = -\frac{49}{9} +\frac{80}{12} \\ x =- \frac{196}{36} +\frac{240}{36} \\ x = \frac{44}{36} \\ x = \frac{11}{9} \\ x = 1\frac{2}{9}

Похожие вопросы
Предмет: Информатика, автор: samkoila99
Предмет: История, автор: Popka36